Development of the Nepalese Financial System: Need for the Formulation of a Master Plan - Matangi Maskay, Nephil; Subedi, Satyendra Raj (NRB Economic Review, 2009)
The paper examines the development of Nepalese financial system which is categorized into three different phases: the first phase is the pre-NRB period; the second phase starts with NRB Act of 1955, which is further disaggregated into two sub-periods at 1984, the start of domestic financial liberalization; and the third and ongoing phase starts after enactment of current NRB Act of 2002. After analyzing period aggregate data on the financial system, the paper concludes that despite significant financial deepening in the context of financial liberalization and integration with the external economy, there is still scope for geographically balanced financial development. For addressing these challenges in a comprehensive manner, the study proposes initiating the development of a Financial Sector Master Plan.